Penamaan Motif Tenun Troso di Desa Troso Kecamatan Pecangaan Kabupaten Jepara (Kajian Etnolinguistik) - ., Zuliati; Kurnia, Ermi Dyah (Sutasoma : Jurnal Sastra Jawa, 2019)
Troso Weaving is a wealth of ancestral heritage that must always be preserved so as to strengthen the nation's identity. In addition, Troso weaving can be a container for various activities that have a positive impact on society. Troso Weaving is not just an aesthetic handicraft product, but also has a function contained in the names of Troso woven motifs. This research aims to: 1) The description of the shape of the lingual unit in Troso woven motifs in Troso Village, Pecangaan District, Jepara Regency. 2) Description of the lexical and cultural significance of Troso woven motifs in Troso Village, Pecangaan District, Jepara Regency. 3) Description of the language function of the cultivation of Troso woven motifs in Troso Village, Pecangaan District, Jepara Regency. It can be concluded that 1) Based on the shape, the names of Troso woven motifs are in the form of words and phrases. 2) Based on the meaning, the names of Troso woven motifs have a lexical meaning and a cultural meaning. 3) Based on the language function, the names of Troso weaving motifs are as a form of respecting the names of characters, as a form of identity, describing flora, depicting fauna, as a form of religious symbolization, as a symbol of calculation, describing the attitude of mutual cooperation, showing social status, showing technology, describe traditional arts, describe ecologically, and as a source of inspiration.Keywords: form, lexical meaning, cultural meaning, language function, names of woven motifs